Neuroanatomical predictors of complex skill acquisition during video game training - Kovbasiuk, Anna; Lewandowska, Paulina; Brzezicka, Aneta; Kowalczyk-Grębska, Natalia (Frontiers in Neuroscience, 2022)
It is known that the outcomes of complex video game skill acquisition are correlated with individual differences in demographic and behavioral variables, such as age, intelligence and visual attention. However, empirical studies of the relationship between neuroanatomical features and success in video game training have been few and far between. The present review summarizes existing literature on grey matter and white matter correlates of complex video game skill acquisition as well as explores its relationship with neuroplasticity. In particular, since age can be an important factor in the acquisition of new cognitive skills, we present studies that compare different age groups (young and old adults). Our review reveals that grey matter in subcortical brain areas predicts complex VG learning outcomes in young subjects, whereas in older subjects the same is true of cortical frontal areas. This may be linked to age-related compensatory mechanisms in the frontal areas, as proposed by The Scaffolding Theory of Aging and Cognition. In the case of plasticity, there is no such relationship - in the group of younger and older adults there are changes after training in both cortical and subcortical areas. We also summarize best practices in research on predictors of video game training performance and outline promising areas of research in the study of complex video game skill acquisition.